Mendorong Penerapan Pendidikan Antikorupsi di Perguruan Tinggi - Tri Anggoro Mukti (Perspektif Hukum, 2018)
This study tries to analyse the effort to combat corruption through anti-corruption lecture program in university. Using a descriptive analytical technique this study attemps to put the lecture as a medium for four principle of education: learning to know, learning to do, learning to live and learning to be. Such education need to be integrate within the anti-corruption values to put corruption as common enemy fo all. The output of this class is hopefully to form a person who say no to corruption proudly and spread the positive attitude of anti-corruption behaviour.